Understanding & Communicating Business Program Outcomes through Visualization and Mapping - Kelli Schutte (Academic Chairpersons Conference Proceedings, 2016)
This session will share the process and outcome of a business program curriculum assessment. The assessment includes conceptual frameworks, curriculum mapping and data visualization to convey results. The process of developing the plan, collecting data and conveying results will be shared.
Keywords: Assessment; framework; data collection; data visualization; communication